Eksplorasi Minat Investasi Cryptocurrency dari Dimensi Keperilakuan - Gusi Putu Lestara Permana; Kadek Srestiyani (Universitas Swadaya Gunung Jati, 2026)
The rapid development of information technology and the advent of the Fourth Industrial Revolution have significantly transformed the way society conducts financial transactions. Cryptocurrency, as an innovation within the digital financial system, offers both convenience and efficiency; however, it also faces considerable challenges concerning security and privacy. This study aims to measure behavioral intentionstoward cryptocurrency investment. Employing construct from theoretical approach based on the Unified Theory of Acceptance and Use of Technology 2 (UTAUT 2) and the Theory of Planned Behavior (TPB), the research analyzes the influence of various behavioral factors on cryptocurrency investment interest. A purposive sample of 120 respondents from Java and Bali was surveyed using a Likert-scale questionnaire, and data were analyzed with Partial Least Squares (PLS) via SmartPLS. The results indicate that interest in cryptocurrency investment can be explained through behavioral dimensions assessed using the UTAUT 2 and TPB models. The key factors examined include trust, awareness, hedonic motivation, and social influence. Investment decisions in cryptocurrency media require strong personal trust and awareness; moreover,external influences, such as social factors, also significantly affect investment interest.